Consistency between Impedance Technique and Echocardiogram Hemodynamic Measurements in Neonates - Wu, Wenshen; Lin, Sulian; Xie, Caixuan; Li, Jianbo; Lie, Jingen; Qiu, Shuyi (American Journal of Perinatology, 2020)
Objective The aim of this study was to validate impedance technique (IT) by investigating the agreement in cardiac output measurements performed by IT and echocardiography (ECHO).Study design This is a prospective observational study, including a total of 30 neonates who underwent hemodynamic measurements by IT and ECHO. To determine the agreement between both methods, we performed IT to measure stroke volume (SV-IT) and cardiac output (CO-IT) immediately before or after ECHO to measure SV (SV-ECHO) and CO (CO-ECHO). The precision and accuracy of the IT relative to ECHO were assessed.Results SV-ECHO and SV-IT were (4.45 ± 0.78) and (4.54 ± 0.81) mL, respectively. The bias and limits of agreement of SV-IT were 0.09 mL and ( –1.92 to 1.73) mL, respectively. The true precision of SV-IT was 27.3%. Furthermore, CO-ECHO and CO-IT were (0.62 ± 0.12) and (0.61 ± 0.12) L/min, respectively. The bias and LoA of CO-IT were 0.01L/min and (–0.33 to 0.31) L/min, respectively. The true precision of CO-IT was 28.3%.Conclusion Agreement between the IT and ECHO in the cardiac output measurement appeared acceptable. However, the accuracy and precision of the IT approach should be further investigated using a larger sample.
Keywords: impedance technique; echocardiogram; cardiac output; Bland–Altman analysis